Identification of heat stress-related genomic regions by genome-wide association study in Solanum tuberosum - Kaier, Alexander; Beck, Selina; Ingold, Markus; Corral García, José María; Reinert, Stephan; Sonnewald, Uwe; Sonnewald, Sophia (Genomics, 2024)
The climate crisis impairs yield and quality of crucial crops like potatoes. We investigated the effects of heat stress on five morpho-physiological parameters in a diverse panel of 178 potato cultivars under glasshouse conditions. Overall, heat stress increased shoot elongation and green fresh weight, but reduced tuber yield, starch content and harvest index. Genomic information was obtained from 258 tetraploid and three diploid cultivars by a genotyping-by-sequencing approach using methylation-sensitive restriction enzymes. This resulted in an enrichment of sequences in gene-rich regions. Population structure analyses using genetic distances and hierarchical clustering revealed strong kinship but weak overall population structure cultivars. A genome-wide association study (GWAS) was conducted with a subset of 20 K stringently filtered SNPs to identify quantitative trait loci (QTL) linked to heat tolerance. We identified 67 QTL and established haploblock boundaries to narrow down the number of candidate genes. Additionally, GO-enrichment analyses provided insights into gene functions. Heritability and genomic prediction were conducted to assess the usability of the collected data for selecting breeding material. The detected QTL might be exploited in marker-assisted selection to develop heat-resilient potato cultivars.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Abiotic stress; GBS; GWAS; Mixed models; Potato; Tetraploid